Adverbial Clauses in Journalistic Style - Machová, Renata (Univerzita Pardubice, 2012)
This bachelor paper clarifies the use of adverbial clauses in journalistic style. The theoretical part firstly discusses a role of subordinate clauses, then the term adverbial clause is introduced and finally, the particular semantic types of adverbial clauses are examined. The whole part forms a basis for the practical part studying the frequency of occurrence of particular semantic clauses and other characteristic properties from samples of adverbial clauses selected from journalistic articles. The aim of the thesis to accomplish is to examine and determine the most frequent clauses within the journalistic style and evaluate overall research findings.
Vedlejší věty příslovečné v anglickém žurnalistickém stylu
Keywords: anglický jazyk; lingvistika; analýza; vedlejší věty příslovečné; žurnalistický styl; English language; linguistics; adverbial clauses; journalistic style